THE ROLE OF NOTARIES IN ILLEGAL FISHING-BASED SALE AND PURCHASE TRANSACTIONS: A STUDY OF PROFESSIONAL LAW AND ETHICS - Moertiono, R Juli; Lubis, Muhammad Syukran Yamin (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
This study discusses the role of notaries in buying and selling transactions related to illegal fishing practices, reviewed from the perspective of law and professional ethics. Illegal fishing is a fishing activity that violates legal regulations, so that it can have a legal impact on the transaction of buying and selling the catch. A notary, as a public official, has a responsibility to ensure that the deeds he or she makes do not conflict with the law and ethics. This research uses a normative juridical method with a legislative and conceptual approach. Data was obtained through literature studies by researching relevant laws and regulations, legal doctrines, and the notary profession code of ethics. The analysis was carried out to identify the extent to which notaries play a role in preventing the legalization of transactions that have the potential to involve the proceeds of illegal fishing. The results of the study show that notaries have an important responsibility to ensure the legality of the object of the transaction, including ensuring that the fishery products traded do not come from illegal fishing activities. In terms of professional ethics, notaries are obliged to reject the making of deeds involving the results of these illegal practices. However, the lack of transparency and oversight of the supply chain of fishery products is often an obstacle. This study recommends strengthening regulations and training for notaries to understand issues related to illegal fishing